A study on depression and anxiety among university students during ODL / Rafizah Kechil, Nor Hanim Abd Rahman and Noor 'Aina Abd Razak - Kechil, Rafizah; Abd Rahman, Nor Hanim; Abd Razak, Noor 'Aina (Universiti Teknologi MARA, Pulau Pinang, 2022)
The majority of universities implemented remote learning, also known as open and distance learning (ODL), amid the Malaysian government's movement control orders (MCO) during the coronavirus disease (COVID-19) pandemic. There are various challenges and issues that lecturers and students have to deal with, in order to ensure the success of ODL or remote learning. Issues of depression and anxiety of university students have also been reported and the rate is alarming especially during the lockdown. Thus, this study focuses on understanding the underlying problems that occur during the MCO. A quantitative approach was applied, with 191 questionnaires collected through Google-form application. The depression and anxiety of university students were measured using a tool called Psychosomatic Symptoms Questionnaire-5 (PSQ-5), which was adopted using the COVID-19's e-Learning Digital Tools questionnaire (CeLDT) and the Patient Health Questionnaire-4 (PHQ-4). The findings revealed that respondents were classified as having "severe" depression and anxiety during the COVID-19 pandemic.